Predicting student translators' performance in machine translation post-editing: interplay of self-regulation, critical thinking, and motivation. Issue 1 (2nd January 2023) - Yang, Yanxia; Wang, Xiangling
ABSTRACT: Machine translation post-editing (MTPE) has become a common practice in translation industry, which calls much attention in academia. However, little research has been carried out to investigate students' cognitive and motivational individual differences in MTPE. The purpose of the present study was to examine the predictive effects of self-regulation, critical thinking, and motivation on students' MTPE performance. Self-reported data was collected from 109 student translators before and after the post-editing test. Partial least squares structural equation modeling (PLS-SEM) was employed to calculate the data. The findings indicated that self-regulation exerted a direct and positive effect on MTPE performance ( β  = .48, p  < .001) and was further statistically affected by critical thinking ( β  = .46, p  < .001) and motivation ( β  = .43, p  < .001). However, no significant effects were found either from motivation or critical thinking on MTPE performance. To train students with heightened levels of self-regulation is crucial in MTPE teaching and learning.